2020
DOI: 10.1108/tlo-06-2020-0117
|View full text |Cite
|
Sign up to set email alerts
|

A learner-centric model of learning organizations

Abstract: Purpose This paper aims to contribute by placing the missing “learner agent” within the entire process of learning. To understand under what social conditions, it is possible to develop autonomous learners who are conscious of self, able to reflect on their identities, roles and responsibilities, to learn and develop professionally, in alignment with the organizational goals and objectives. Design/methodology/approach The paper uses empirical data from a higher educational institution to provide insights on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Several studies addressed the role of the learner and considered how this might influence the learning process. One such study [14] looked at a learner-centric model and examined ways in which employees become learning agents responsible for their own learning. They found that in order to succeed as learning agents, the employees should have had some time to develop their identities, that is, it did not work so well with young and inexperienced employees.…”
Section: • Self-driven Learnersmentioning
confidence: 99%
“…Several studies addressed the role of the learner and considered how this might influence the learning process. One such study [14] looked at a learner-centric model and examined ways in which employees become learning agents responsible for their own learning. They found that in order to succeed as learning agents, the employees should have had some time to develop their identities, that is, it did not work so well with young and inexperienced employees.…”
Section: • Self-driven Learnersmentioning
confidence: 99%
“…The learning organisation also reflects the mastery of knowledge gained from implementing and adopting new information, instruments, or approaches related to self-transformation (White & Burton, 2007). Akella (2021) also conducted an empirical research to demonstrate the significance of learner agents and the positive outcomes associated with autonomous learning choices and processes designed with minimal structural influence.…”
Section: Learning Organisation and Iwbmentioning
confidence: 99%
“…Skills to function effectively in modern workstations evolve and necessitate individuals who have the purchasing power to look forward to updating their skill sets continuously. Eventually, it increases the number of adult learners looking for HEIs to obtain a credential that will grant entrance to their professional hierarchy (Akella, 2021). Furthermore, selecting a program of studies also relies on survival prospects in a global knowledge economy.…”
Section: Readiness Of the Heismentioning
confidence: 99%